La nécessaire praxis de la pensée et du dialogue critiques en classe - Marie-France Daniel (Recherches en Éducation)
In this paper, I will first present the pragmatist conception of “responsible education”; which has its foundations in the interrelation between experience, communication and critical reflection. Then, I will question critical thinking as it is manifested by pupils: Is it a product or a process? Does its development presuppose irreversible stages? What are the obstacles to its mobilization? Finally, I will present distinctions between elements associated with discursive competencies, namely: narration, conversation, discussion, non-critical dialogue and critical dialogue.